A modified scar model with controlled tension on secondary wound healing in mice. Issue 1 (6th May 2020) - Wang, Zi; Huang, Xin; Zan, Tao; Li, Qingfeng; Li, Haizhou
Abstract: Pathological scars might cause a distorted appearance and restricted mobility, and the study of scar pathophysiology has been hindered by the absence of a reliable model. In this study, we introduce a model with a modified device to induce controlled tension on a wound healing by secondary intention to overcome the shortcomings of the model generated by Aarabi et al . We investigated and recommend an induction of 0.1 N/mm 2 tension on day 7 for 14 days to mimic the characteristics of human scars. A 3.5-fold increase in scar tissue and a 2-fold increase in collagen production were induced by the modified model. Histologically, the modified method increased scar thickness. However, no significant difference was found in cell density between the two groups. This modified procedure significantly increased scar tissue, which could be used for further cellular and biomolecular research. The mechanical force applied to the wound became measurable and controllable. This method is more convenient for researchers to observe in real-time and for providing timely adjustments of the tension used in this modified model.